Welfare, but Only for Us? Randomized Survey Experiment on Welfare Chauvinism Conducted on Students in Brno (Politeja, 2019)
Welfare, but Only for Us? Randomized Survey Experiment on Welfare Chauvinism Conducted on Students in BrnoThe immigrants’ rights to welfare benefits have been heavily discussed in European Union member states recently. This study focuses on general opposition to those rights, welfare chauvinism, and its potential existence in the country with essentially no immigration issues – the Czech Republic. Using a survey experiment on students of Masaryk University in Brno, a change in the attitudes towards the child benefits (as one aspect of social benefits) was observed right after they were reminded that also immigrants from other countries have accessto those benefits. The effect of persuasive argument was stronger in the case of Bulgarian rather than German immigrants, which could imply Czechs perceive Germans more positively than they do Bulgarians, and they behave less chauvinistically towards them in comparison to citizens of Bulgaria.